Key to robust workforce lies in keeping experience and skills - Harris, Colleen (InFinance, 2011)
The global financial crisis has brought home the importance of retaining employees heading for retirement as long as possible because of their knowledge, corporate memory and experience managing business and risk at uncertain times.